Feline Adipose Derived Multipotent Stromal Cell Transdifferentiation Into Functional Insulin Producing Cell Clusters - Taguchi, Takashi; Duan, Wei; Wolfson, Wendy; Duhon, Brandy; Halphen, Emily G.; Lopez, Mandi J. (Frontiers in Bioengineering and Biotechnology, 2022)
Diabetes mellitus is one of the most prevalent feline endocrinopathies, affecting up to 1% of pet cats. De novo generation of functional insulin producing cell (IPC) clusters via transdifferentiation of adipose-derived multipotent stromal cells (ASCs) may provide viable, functional, autologous cells. Cells were induced to form IPCs using a novel, three-stage culture process with stromal or differentiation medium under static and dynamic conditions. Clusters were evaluated for intracellular zinc, viability, intracellular insulin, glucagon, and somatostatin, ultrastructure, glucose-stimulated insulin secretion in the presence or absence of theophylline, proteomics, and gene expression. Isolated cells were multipotent, and cell clusters cultured in both media had robust cell viability. Those cultured in differentiation medium contained zinc and mono- or polyhormonal α-, β-, and δ-like cells based on immunohistochemistry labeling and Mallory-Heidenhan Azan-Gomori’s staining. Ultrastructurally, cell clusters cultured in differentiation medium contained insulin granules within vesicles, and clusters had a concentration-dependent insulin response to glucose in the presence and absence of theophylline which increased both insulin secretion and intracellular content. Expression of NK6.1, Pax6, Isl1, Glut2, RAB3A, glucagon, insulin, and somatostatin increased with differentiation stage for both sexes, and expression of nestin at stages 1 and 2 and Neurod1 at stage 2 was higher in cells from female donors. The cluster insulin secretion responses and endocrine and oncogene gene expression profiles were inconsistent with insulinoma behavior. A total of 180 proteins were upregulated in differentiated clusters, and the majority were associated with biological regulation, metabolic processes, or stimulus response. Dynamic culture resulted in clusters composed primarily of insulin expressing cells that had higher glucose-stimulated insulin secretion than those in static culture. Collectively, the results of this study support de novo generation of functional IPC clusters from feline ASCs isolated from tissues removed during routine sterilization. Further, cluster functionality is enhanced with dynamic, motion-driven shear stress. This work establishes a foundation for development of IPC therapies for short or long-term diabetes management and may represent an option for models to study diabetes prevention and treatment across species.